Fatigue behavior and lifetime assessment of an austenitic stainless steel in the VHCF regime at ambient and elevated temperatures. Issue 5 (8th February 2023) - Schopf, Tim; Weihe, Stefan; Daniel, Tobias; Smaga, Marek; Beck, Tilmann
Abstract: While the LCF behavior of austenitic steels used in nuclear power plants is already well investigated, the VHCF regime has not been characterized in detail so far. For this, fatigue tests on the metastable austenitic steel AISI 347/1.4550 were performed with a servo‐hydraulic testing system at test frequencies up to 980 Hz and with an ultrasonic fatigue testing system at a test frequency of 20, 000 Hz. To compare these test results to the ASME standard fatigue curve (total strain amplitude vs. load cycles to failure), a fictitious‐elastic and an elastically plastic assessment method was used. The elaborated elastic–plastic assessment method generates good results, while a purely elastic assessment in the VHCF regime, commonly used in literature, leads to significantly nonconservative results. Moreover, phase transformation from metastable austenite into stable α′‐martensite can take place, and no specimen failure occurs in the VHCF regime. Consequently, for this material, a real endurance limit exists. Highlights: AISI 347 shows a significant plastic strain component in the VHCF regime. Elastic–plastic FE‐analysis describe cyclic material behavior in the VHCF regime accurately. An elastic–plastic based calculation method was elaborated to be able to assess fatigue lifetime. Results of the assessment method show a good accordance to experimental tests and the ASME code fatigue curve.